Randomly amplified polymorphic DNA (RAPD) fingerprinting of Indian sheep breeds* - KUMAR, K GANESH; KUMAR, PUSHPENDRA; KUMAR, SANJEEV; BHATTACHARYA, T K; BHUSHAN, B; AHLAWAT, S P S (The Indian Journal of Animal Sciences, 2014)
Variation in the DNA fingerprint of Indian sheep breeds, viz. Madras Red, Mandya, Marwari and Muzaffarnagari were analyzed by RAPD-PCR technique to estimate the genetic relatedness and diversity within and between breeds. The DNA isolated by phenol extraction method was analyzed using 6 random primers, All the 6 primers amplified satisfactorily and 4 of them were used to produce polymorphic patterns. The data so generated was used to estimate band sharing frequency (BSF), mean average percentage difference (MAPD) and genetic distance among the breeds. Within breed BSF was highest in Mandya and between breed BSF was highest between Mandya and Madras Red breeds. Marwari was most distant from rest ofthe 3 breeds by genetic distance estimate. This study generated the basic RAPD fingerprint data in the above sheep breed.